Pirates of the Caribbean. On stranger tides [videorecording (Blu-ray + DVD)] - Marshall, Rob; Depp, Johnny; Cruz, Penélope; Rush, Geoffrey, 1951-; McShane, Ian, 1942-; Elliott, Ted; Rossio, Terry (Touchstone Home Entertainment, 2011)
A tale of truth, betrayal, youth, demise, and mermaids! When Jack crosses paths with a woman from his past, he's not sure if it's love, or if she's a ruthless con artist using him to find the fabled Fountain of Youth. Forced aboard the ship of the most feared pirate ever, Jack doesn't know whom to fear more, Blackbeard or the woman from his past.